A History of Childhood Maltreatment and Intimate Partner Violence Victimization Among Native American Adults. Issue 18 (September 2018) - Kong, Jooyoung; Roh, Soonhee; Easton, Scott D.; Lee, Yeon-Shim; Lawler, Michael J.
This study examined the association between childhood maltreatment and intimate partner violence (IPV) victimization among Native American adults. Based on Riggs's theoretical model of the long-term effects of childhood abuse, we also examined the mediating roles of insecure attachment patterns and depressive symptoms. The current study was a secondary data analysis using the 2013 General Well-Being Among Native Americans dataset ( N = 479). Structural equation modeling was used to examine the hypothesized relationships among key constructs. Consistent with existing literature of revictimization, our findings showed that the experience of childhood maltreatment was positively associated with IPV victimization. Mediation analyses indicated that depression was a significant mediator in the association between childhood maltreatment and IPV victimization. In addition, all the paths linking childhood maltreatment, fearful attachment, depressive symptoms, and IPV victimization were statistically significant, although the overall mediation effect was not significant. The results of this study suggest that Riggs's model can serve as a useful theoretical framework for understanding the long-term effects of childhood maltreatment among Native American adults. Practitioners in the area of IPV should include maltreatment history and current attachment patterns in client assessments, which could help address conflict and violence within intimate relationships.